Kabbalah and Queer Theology: Resources and Reservations - Michaelson, Jay (Theology & sexuality, 2012)
In the last few decades, Kabbalah has enjoyed an unlikely resurgence, both in popular culture and among feminist and queer theologians interested in alternatives to traditional Western religious discourse. Yet theosophical Kabbalah is also an outrageously heteronormative discourse. Is it possible to attempt queer readings of Kabbalistic text and symbolism that are of use to a reflective queer theology? This essay proposes three such readings, focusing on some Kabbalistic constructions of gender dimorphism. First, the essay notes the constructed nature of gender in Kabbalistic text, in which males may have predominantly feminine genders, all people have both genders within them, and the ideal is not a butch masculine and femme feminine, but a combination of them. To illustrate this point, the essay reads the Kabbalistic understanding of the binding of Isaac in the context of S/M. Second, the essay discusses the role of yichud, unification, particularly when male mystics take the role of the feminine sefirah of Malchut, imitating God, who is, via the Sefirot, a multi-gendered, trans-gendering deity wearing the masks of different genders at different times, and seeking partners who do the same. And third, the essay discusses the symbolic feminization of the male body through circumcision, engaging critically with the thought of Elliot Wolfson and reading circumcision as an inscription of “negative space” that links Kabbalistic gender play with unio mystica. This drama of androgynization can be (re)configured not in terms of totality, but of infinity — precisely because the phallic pretension to completeness has been circumcised.